A new approach to stabilize the electrochemical performance of Li metal batteries through the structure alteration of CNT scaffolds. (25th January 2023) - Kim, Junghwan; Choi, Junghyun; Kim, Patrick Joohyun
Abstract: Recently, interest in Li-metal batteries (LMBs) has been revived because the high specific capacity and lowest operating potential of Li-metal anodes help in resolving the existing issues of conventional Li-ion batteries. Unfortunately, the main problems associated with poor coulombic efficiency and dendritic Li formation impede the use of Li-metal anodes for commercial batteries. Among various strategies to address these intrinsic challenges of Li-metal anodes, the approach to utilize 3D current collectors has shown attractive results in terms of electrochemical stability. Herein, we assessed two different carbon nanotubes (e.g., double-walled nanotubes (DWNTs) and multi-walled nanotubes (MWNTs) scaffolds to study how the structure of carbon-based current collectors affects the coulombic efficiency and electrochemical stability of LMBs. As MWNTs have a more favorable structure for the reversible storage/release of Li-ion than DWNTs, they facilitate uniform and stable Li deposition over the entire surface of the MWNT matrix, thereby diminishing the growth of sharp dendritic Li. This resulting effect directly contributes to the stable operation of Li-metal cells at high current densities. Moreover, it has shown a remarkable improvement in electrochemical stability when the MWNT current collector was applied to the anode-free cell using a LiCoO2 cathode. The MWNT/LiCoO2 cell exhibited excellent cycle retention (97% at 50 cycles) with a high coulombic efficiency (99%). This work suggests that the material of the current collectors plays an apparently important role in the electrochemical stability of LMBs. Graphical abstract: Image 1 Highlights: CNT scaffolds were used as 3D current collectors for Li-metal batteries (LMBs). Double-walled nanotubes (DWNTs) and multi-walled nanotubes (MWNTs) were employed. MWNT current collectors enabled more uniform Li deposition than DWNT current collectors. Half- and full-cells with the MWNT current collector exhibited excellent performances.